INCREASE UNDERSTANDING OF IT-BASED ACCOUNTING FOR MAIDA AQUATIC - Imam Muslim, Ade; Widiastuty, Tri; Nur Hanifah, Anna Saadyah (LPPM Univ. Ibn Khaldun Bogor, 2023)
Maida Aquatic is a type of business that is included in the Micro, Small and Medium Enterprises (MSMEs). Maida Aquatic's operational activities are selling all types of fish, fish food, aquariums and other equipment related to fisheries. Maida Aquatic was founded in 2017. At the beginning it only sold a few types of ornamental fish, as time went on Maida Aquatic was able to increase sales by adding more types of ornamental fish and selling fish food and equipment related to fish. However, business development was not followed by the financial administration system so that it was not recorded properly. In an effort to overcome these problems, we recommend several solutions, namely accounting training according to EMKM standards, Accurate training, and creating social media as an online promotion tool. The results of the service will be analyzed through nonparametric statistics using a questionnaire approach to measure the success rate of this service. The results of the community service activities have positive implications for partners in developing bookkeeping. Partners understand the accounting standards that must be applied, are able to prepare financial reports and analyze financial data simply.